1993
DOI: 10.2337/diacare.16.11.1485
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria in a Middle-Aged Workforce: Effect of hyperglycemia and ethnicity

Abstract: Of the variables investigated, hyperglycemia was the most important factor explaining the high prevalence of microalbuminuria in Maori and Pacific Islander workers compared with the European workers. However, only 14.9% of the variation in urinary albumin concentrations was found in our multivariate model, and we have speculated on the contribution of other factors such as diet and coexisting renal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…We indeed found positive associations between UAE and age, BP, BMI, and plasma glucose in both genders, but we only observed gender differences in these relations in age, BMI, and plasma glucose. Finally, Metcalf et al (16,17), in their multivariate regression model to predict urinary albumin concentration mentioned the interaction of BMI and gender. Unfortunately, this interaction was not further explored in the results of the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We indeed found positive associations between UAE and age, BP, BMI, and plasma glucose in both genders, but we only observed gender differences in these relations in age, BMI, and plasma glucose. Finally, Metcalf et al (16,17), in their multivariate regression model to predict urinary albumin concentration mentioned the interaction of BMI and gender. Unfortunately, this interaction was not further explored in the results of the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Microalbuminuria was de®ned as a urinary albumin concentration b 28 mg/L for males and b 28 mg/L for females and a high albumin:creatinine ration as b 2.25 mg/mol for males and b 2.78 mg/mol for females based on reference intervals determined from the same population. 15 Reference intervals were the 2.5th and 87.5th percentiles determined from participants after excluding those with Albustix positive albuminuria, diabetes mellitus, bac- …”
Section: Analysesmentioning
confidence: 99%
“…18 By comparison, Allawi et al 5 reported microalbuminuria in 26% of Asian Indian people with NIDDM, Collins et al 6 reported prevalences of 26% in men and 30% in women from the Paci®c Island of Nauru, Haffner et al 8 reported a prevalence of microalbuminuria of 13% in non-diabetic Mexican Americans, Robbins et al 19 reported prevalences in American Indians of 28.3% in Arizona, 15.1% in Oklahoma and 13.8% in North and South Dakota, and we have reported prevalences of microalbuminuria in European, Maori, Paci®c Island and Asian New Zealanders of 2.7%, 15.6%, 13.0% and 8.0%, respectively. 15 There is no simple explanation for the ethnic differences in prevalences of microalbuminuria. In the New Zealand study, glycaemia was the most signi®cant determinant of urinary albumin concentrations in a multivariate model including blood glucose levels, age, gender, ethnic group, body mass index, blood pressure, blood lipid levels, cigarette smoking, and alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest specific, early damage of podocytes and, particularly, of the slit diaphragm as a consequence of diabetes. Type 2 diabetic patients may already have microalbuminuria at the time of diagnosis, as may healthy subjects with impaired glucose tolerance [19] and insulin resistance [20]. We investigated whether the offspring of type 2 diabetic patients, who are prone to diabetes, exhibit podocyte protein nephrin in urine in association with insulin resistance.…”
Section: Introductionmentioning
confidence: 99%